Milk and Dairy Product Consumption and Risk of Mortality: An Overview of Systematic Reviews and Meta-Analyses. (15th May 2019) - Cavero-Redondo, Ivan; Alvarez-Bueno, Celia; Sotos-Prieto, Mercedes; Gil, Angel; Martinez-Vizcaino, Vicente; Ruiz, Jonatan R
ABSTRACT: The effect of dairy product consumption on health has received substantial attention in the last decade. However, a number of prospective cohort studies have shown contradictory results, which causes uncertainty about the effects of dairy products on health. We conducted an overview of existing systematic reviews and meta-analyses to examine the association between dairy product consumption and all-cause mortality risk. A literature search was conducted in MEDLINE (via PubMed), EMBASE, the Cochrane Central Database of Systematic Reviews, and the Web of Science databases from their inception to April, 2018. We evaluated the risk of bias of each study included using the AMSTAR 2 tool. The risk ratios (RRs) for each meta-analysis were displayed in a forest plot for dose-response and for high compared with low dairy consumption. The initial search retrieved 2154 articles; a total of 8 meta-analyses were finally included after applying the inclusion and exclusion criteria. The number of included studies in each meta-analysis ranged from 6 to 26 cohort studies, which reported data from 6–28 populations. The sample sizes varied across studies from 24, 466 participants reporting 5092 mortality cases to 938, 817 participants reporting 126, 759 mortality cases. After assessing the risk of bias, 25% of the studies were categorized as acceptable, 25% as good, and 50% as very good. The RRs reported by the meta-analyses ranged from 0.96 to 1.01 per 200 g/d of dairy product consumption (including total, high-fat, low-fat, and fermented dairy products), from 0.99 to 1.01 per 200–244 g/d of milk consumption, and from 0.99 to 1.03 per 10–50 g/d of cheese consumption. The RR per 50 g/d of yogurt consumption was 0.97 (95% CI: 0.85, 1.11). In conclusion, dairy product consumption is not associated with risk of all-cause mortality. This study was registered in PROSPERO as CRD42018091856.